2004
DOI: 10.1113/jphysiol.2004.068197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on endothelium‐derived nitric oxide function in humans

Abstract: Vascular endothelial function is essential for maintenance of health of the vessel wall and for vasomotor control in both conduit and resistance vessels. These functions are due to the production of numerous autacoids, of which nitric oxide (NO) has been the most widely studied. Exercise training has been shown, in many animal and human studies, to augment endothelial, NO-dependent vasodilatation in both large and small vessels. The extent of the improvement in humans depends upon the muscle mass subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
636
6
28

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 811 publications
(727 citation statements)
references
References 245 publications
38
636
6
28
Order By: Relevance
“…An increase in shear stress (eg, during physical activity) has been proved to enhance eNOS mRNA and protein expression and promote phosphorylation of the serine 1177 residue of the enzyme, thereby boosting vascular NO production 31, 32, 33, 34. However, animal studies suggest that after a few months of exercise training, eNOS expression levels reduce to the preexercise state 35. This decline is explained by the fact that the normalization of shear stress at an early adaptive state requires a decline in vascular tone and, hence, vasodilatation; however, this change does not occur at a later stage when the vessels have already grown 1…”
Section: Adaptation Of Coronary Circulation To Exercise Training In Tmentioning
confidence: 99%
“…An increase in shear stress (eg, during physical activity) has been proved to enhance eNOS mRNA and protein expression and promote phosphorylation of the serine 1177 residue of the enzyme, thereby boosting vascular NO production 31, 32, 33, 34. However, animal studies suggest that after a few months of exercise training, eNOS expression levels reduce to the preexercise state 35. This decline is explained by the fact that the normalization of shear stress at an early adaptive state requires a decline in vascular tone and, hence, vasodilatation; however, this change does not occur at a later stage when the vessels have already grown 1…”
Section: Adaptation Of Coronary Circulation To Exercise Training In Tmentioning
confidence: 99%
“…Cerebrovascular vasodilatation in response to hypercapnia is, in part, dependent upon NO bioavailability (Peebles et al 2007). Nitric oxide has been reported to increase with exercise training (Green et al 2004;Kingwell et al 1997). Exercise training has also been shown to increase systemic endothelium-dependent vasodilatation (a NO-mediated response) (Green et al 2004;Clarkson et al 1999;Tinken et al 2008).…”
Section: Effect Of Training On Resting Variablesmentioning
confidence: 99%
“…One cross-sectional study indicated that higher fitness is related to larger frontal and temporal volumes of grey matter (Colcombe et al 2006). Other potential mechanisms may involve more endotheliumdependent vasodilatation as a result of more NO bioavailability (Green et al 2004) and/or cerebral angiogenesis (Rhyu et al 2010;Swain et al 2003;Ding et al 2006;Black et al 1990). In support of this, ageinduced cerebral atrophy appears to be less marked in those with higher aerobic fitness (Colcombe et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that improvement in vascular function after dynamic exercise training is not universal (Green et al 2004;Green et al 2011), especially in healthy volunteers. The presence of time-dependent adaptations in vascular function in response to exercise training may partly explain this observation.…”
Section: Introductionmentioning
confidence: 96%
“…The presence of time-dependent adaptations in vascular function in response to exercise training may partly explain this observation. Originally based on findings in animals (Laughlin 1995), human studies have also demonstrated that short-term exercise training enhances conduit artery function in subjects with cardiovascular risk factors or disease (Green et al 2004;Maiorana et al 2001;Watts et al 2004), whilst prolonged training induces structural changes (i.e. increased diameter) (Brown 2003;Prior et al 2003).…”
Section: Introductionmentioning
confidence: 99%